Formulation and Evaluation of Anti-Acne Activity of Gel Pineapple Peel (Ananas comosus L.) Extract on the Growth of Propionibacterium acnes - Latu, Saparuddin; Firman, Imran; Yaqkin-P, Andi Muh.; Musliani, Musliani (Universitas Muslim Indonesia, 2024)
Pineapple peel contains many compounds, namely flavonoids, tannins, saponins, phenolics, steroids, alkaloids and bromelin enzymes. Acne is a chronic inflammatory disease of the pilosebaceous glands. One of the bacteria that causes acne is Propionibacterium acne. Preparations that can be made for anti-acne are gel preparations. This study aims to determine whether the ethanol extract of pineapple peel (Ananas comosus L.) can be made into an anti-acne gel preparation and to find out at what concentration the ethanol extract of pineapple peel (Ananas comosus L.) in an anti-acne gel preparation can provide inhibitory activity on the development of Propionibacterium acne bacteria. This research method is true experimental by making anti-acne gel preparations of pineapple peel extract (Ananas Comosus L.) with various concentrations of 2%, 3%, 5% and testing the activity of the preparation against Propionibacterium acne using the agar well method. The results of the gel preparation formula showed that there were significant differences before and after the cycling test in both organoleptic, homogeneity, pH, viscosity, spreadability and adhesion tests. The activity test results obtained were that the largest inhibition zone was the 5% concentration, namely 12.7 mm, which was in the strong category, while the 3% concentration, which was 11.03 mm, and the 2% concentration, which was 8.8 mm, was included in the moderate category.